Antimicrobial Synergy of Silver-Platinum Nanohybrids With Antibiotics - Ranpariya, Bansi; Salunke, Gayatri; Karmakar, Srikanta; Babiya, Kaushik; Sutar, Santosh; Kadoo, Narendra; Kumbhakar, Pathik; Ghosh, Sougata (Frontiers in Microbiology, 2021)
Various bacterial pathogens are responsible for nosocomial infections resulting in critical pathophysiological conditions, mortality and morbidity. Most of the bacterial infections are associated with biofilm formation, which is resistant to available antimicrobial drugs. As a result, novel bactericidal agents need to be fabricated, which can effectively combat the biofilm-associated bacterial infections. Herein, for the first time we report the antimicrobial and antibiofilm properties of silver-platinum nanohybrids (AgPtNHs), silver nanoparticles (AgNPs), and platinum nanoparticles (PtNPs) against Escherichia coli, Pseudomonas aeruginosa, Bacillus subtilis, and Staphylococcus aureus. The AgPtNHs were synthesized by a green route using Dioscorea bulbifera tuber extract at 100°C for 5 h. The AgPtNHs ranged in size from 20 to 80 nm, with an average of ̴ 59 nm. AgNPs, PtNPs and AgPtNHs showed a zeta potential of -14.46, -1.09 and -11.39 mV, respectively. High antimicrobial activity was observed against P. aeruginosa and S. aureus and AgPtNHs exhibited potent antimicrobial synergy in combination with antibiotics such as streptomycin, rifampicin, chloramphenicol, novobiocin and ampicillin up to variable degrees. Interestingly, AgPtNHs could inhibit bacterial biofilm formation significantly. Hence, co-administration of AgPtNHs and antibiotics may serve as a powerful strategy to treat bacterial infections.